THE DIFFICULTIES FOUND BY PATIENTS IN THE TREATMENT OF NON-MELANOMA SKIN CANCER IN ANÁPOLIS-GO (CIPEEX, 2022)
CANCER IS A VERY STIGMATIZED AND DREADED DISEASE, AMONG THE MOST PREVALENT IN BRAZIL AND THE WORLD, IS NON-MELANOMA SKIN CANCER. IT DIRECTLY INTERFERES WITH PATIENTS' SELF-ESTEEM, AS WELL AS WITH THEIR PERSONAL AND PROFESSIONAL LIVES. IN THE SKIN WE KNOW THAT THE CELLS ARE ARRANGED IN SEVERAL LAYERS, AND DEPENDING ON THE LOCATION, THERE ARE DIFFERENT TYPES OF CANCER, SO THERE ARE TWO MOST COMMON SUBTYPES: BASAL CELL CARCINOMA (CBC) AND SQUAMOUS CELL CARCINOMA (SCC). THEREFORE, IT IS NECESSARY TO STUDY NON-MELANOMA SKIN CANCER, SINCE IT IS THE MOST PREVALENT NEOPLASM IN BRAZIL AND IN THE WORLD, WITH THE GREATEST RISK FACTOR BEING SUN EXPOSURE. IN ADDITION, IT IS NECESSARY TO DEMONSTRATE THE DIFFICULTIES ENCOUNTERED BY THESE PATIENTS, REGARDING THE ONCOLOGICAL TREATMENT BY THE SUS (UNIFIED HEALTH SYSTEM) SINCE THE ADHESION IS OF PARAMOUNT IMPORTANCE IN THE PROGNOSIS OF THE DISEASE. THE OBJECTIVE OF THIS STUDY IS TO STUDY THE PROBLEMS RELATED TO THE PHYSICAL, SOCIAL / FAMILIAL, EMOTIONAL AND FUNCTIONAL WELL-BEING OF PATIENTS WITH NON-MELANOMA SKIN CANCER, COMPARED TO THE TREATMENT IN QUESTION, PERFORMED BY SUS IN ANÁPOLIS-GO. A RETROSPECTIVE AND QUALITATIVE QUANTITATIVE CROSS-SECTIONAL STUDY WILL BE PERFORMED IN NON-MELANOMA SKIN CANCER PATIENTS AT THE ANNAPOLIS CANCER HOSPITAL, WHO WILL ANSWER A SIMPLE QUESTIONNAIRE ABOUT THE DIFFICULTIES ASSOCIATED WITH THE TREATMENT IN QUESTION. IT IS HOPED TO FIND THE POSSIBLE FAILURES IN THE SUS, RELATED TO THE TREATMENT OF SKIN CANCER, TO ELUCIDATE PROPOSALS THAT AFFECT THE IMPROVEMENT OF THEIR QUALITY OF LIFE, REDUCING THE DIFFICULTIES IMPOSED BY THE TREATMENT BUREAUCRACY AND OBTAINING AN IMPROVEMENT IN THEIR ADHERENCE.
Keywords: Skin cancer. Non-melanoma cancer. Squamous cell carcinoma. Basal cell carcinoma.